Most commonly natural and synthetic antihyperlipidemic agents available and distracted in Erbil city - Adham, Aveen Nozad (Zanco Journal of Medical Sciences (ZJMS), 2015)
Background and objective: Hyperlipidemia refers to elevated levels of lipids and cholesterol in the blood, and is also identified as dyslipidemia, to describe the manifestations of different disorders of lipoprotein metabolism. The aim of this study was to investigate the available and commonly distracted natural and synthetic antihyperlipidemic agents in herbal shops, pharmacies and prescribed by physicians in Erbil city, and to determine physicians’ response for the use of natural products. Methods: Between November 2013 to February 2014; 20 herbal shops and 40 pharmacies in Erbil city were visited randomly for asking on available and most commonly distracted natural and synthetic antihyperlipidemic agents. Forty doctors at private clinics were asked about the most frequently prescribed natural and synthetic antihyperlipidemic agents in Erbil city. Results: Of eight synthetic drugs available in pharmacies, statins were considered the first line agents as antihyperlipidemic drugs particularly atorvastatin and rosuvastatin. Of 16 natural products available in Erbil herbal shops and pharmacies, garlic and omega 3 give positive response by patients and highly distracted by pharmacist and herbalist. Of 40 physicians, 27 (68%) prescribe both natural and synthetic agents while only 13 (32%) prescribe synthetic drugs as antihyperlipidemic agents for patients. Conclusion: Statins used in first order as antihyperlipidemic drugs and uses of natural products, as lipid lowering agents in Erbil, is getting larger interest by people, herbalists, pharmacists and doctors. Of 40 doctors, 68% prescribe natural products along with synthetic drugs but also there is a need to educate the people on how to use these natural agents and choice suitable products for them.